2017
DOI: 10.5897/ijps2017.4676
|View full text |Cite
|
Sign up to set email alerts
|

Variability of quiet-time diurnal amplitude and phase of cosmic ray count rates in the mid- and high latitudes

Abstract: Studies have been done on the variability of cosmic rays flux during solar quiet days at mid and high latitudes. By using the 5 quietest days for each month, the monthly mean diurnal variation of cosmic ray anisotropy have been derived for the period 1981 to 2007, which covers part of cycles 21, 22 and 23. These quiet days are days during which the sun is relatively magnetically quiet, leading to less anisotropic behaviour in the diurnal flux of cosmic rays measured on the earth surface. Four stations (Rome, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…The studies of (Modzelewska et al, 2021;Park, 2018) have shown that the diurnal phase tends to shift towards later hours during the maximum solar activity years compared with the minimum solar activity years. Furthermore, Okiyi et al (2017) suggested that phase variation has components of both 22-year and 11-year cycles, influenced by solar polar magnetic field reversal and interplanetary magnetic field strength changes associated with sunspot cycles. These findings collectively highlight the complicated cyclic nature of the phase of cosmic ray diurnal variability.…”
Section: Background and Literature Surveymentioning
confidence: 99%
“…The studies of (Modzelewska et al, 2021;Park, 2018) have shown that the diurnal phase tends to shift towards later hours during the maximum solar activity years compared with the minimum solar activity years. Furthermore, Okiyi et al (2017) suggested that phase variation has components of both 22-year and 11-year cycles, influenced by solar polar magnetic field reversal and interplanetary magnetic field strength changes associated with sunspot cycles. These findings collectively highlight the complicated cyclic nature of the phase of cosmic ray diurnal variability.…”
Section: Background and Literature Surveymentioning
confidence: 99%